Effect of Performance Deficiencies on Graduation and Board Certification Rates: A 10-yr Multicenter Study of Anesthesiology Residents. (July 2016) - Turner, Judi A.; Fitzsimons, Michael G.; Pardo, Manuel C.; Hawkins, Joy L.; Huang, Yue Ming; Rudolph, Maria D. D.; Keyes, Mary A.; Howard-Quijano, Kimberly J.; Naim, Natale Z.; Buckley, Jack C.; Grogan, Tristan R.; Steadman, Randolph H.
Abstract : Background: This multicenter, retrospective study was conducted to determine how resident performance deficiencies affect graduation and board certification. Methods: Primary documents pertaining to resident performance were examined over a 10-yr period at four academic anesthesiology residencies. Residents entering training between 2000 and 2009 were included, with follow-up through February 2016. Residents receiving actions by the programs' Clinical Competency Committee were categorized by the area of deficiency and compared to peers without deficiencies. Results: A total of 865 residents were studied (range: 127 to 275 per program). Of these, 215 residents received a total of 405 actions from their respective Clinical Competency Committee. Among those who received an action compared to those who did not, the proportion graduating differed (93 vs. 99%, respectively, P < 0.001), as did the proportion achieving board certification (89 vs. 99%, respectively, P < 0.001). When a single deficiency in an Essential Attribute ( e.g., ethical, honest, respectful behavior; absence of impairment) was identified, the proportion graduating dropped to 55%. When more than three Accreditation Council for Graduate Medical Education Core Competencies were deficient, the proportion graduating also dropped significantly. Conclusions: Overall graduation and board certification rates were consistently high in residents with no, or isolated, deficiencies. Residents deficient in an Essential Attribute, or multiple competencies, are at high risk of not graduating or achieving board certification. More research is needed on the effectiveness and selective deployment of remediation efforts, particularly for high-risk groups. Abstract : In a review of 865 residents from four U.S. programs with up to 16 yr of follow-up, residents who were deemed deficient in an Essential Attribute or in multiple competencies were at high risk for not graduating or achieving board certification.